Seseli salsugineum (Apiaceae), a new species from Central Anatolia, Turkey - Duran, Ahmet; Samigullin, Tahir; Lyskov, Dmitry (Phytotaxa, 2021)
A new species, Seseli salsugineum A.Duran & Lyskov (Apiaceae), is described from Lake Tuz Gölü area, Central Anatolia, Turkey. The new species is related to S. transcaucasicum and S. libanotis and differs in stem features (up to 200 cm tall and 5‒15 mm ⌀ vs. up to 80 cm tall and up to 6 mm ⌀ or up to 150 cm tall and 10‒20 mm ⌀), stem base pubescence (glabrous vs. densely pubescent or sometimes pubescent), leaf blades pubescence (glabrous with scabrid margin vs. entirely scabrid or glabrous), bracts 0.3‒0.8 mm wide, without membranous margin (vs. 1‒3 mm wide, with membranous margin), umbellules (tight, 5‒12 mm ⌀ vs. not tight 13‒15 mm ⌀ or 5‒6 mm ⌀), stylopodium depressed (not conical), mericarp ridges (finely ridged vs. distinctly ridged), fruit anatomy (vallecular vittae 3 vs. vallecular vittae solitary or 1‒2), habitat (salty marshes and salt steppes vs. grassy meadows, sparse forests, clearings in mountain forests, and subalpine meadows), and distributional range. In addition, S. salsugineum is recognized as a closely related to S. transcaucasicum and S. libanotis species by molecular analysis of nrITS/ETS.